Protective efficacy of a ‘pan-fungal’ vaccination strategy against experimental Pneumocystis infection in drug-immunosuppressed macaques - Rabacal, Whitney; Hu, Anna; Kirton, Gabrielle; Chapman, Taylor I.; Wychrij, Daniel; Oworae, Kwadwo O.; Norris, Karen A. (Frontiers in Immunology, 2026)
IntroductionPneumocystis jirovecii causes life-threatening fungal pneumonia (PJP) and other serious pulmonary sequelae in HIV infected individuals and other immunocompromised populations. In recent years, while the frequency of PJP has declined in HIV infected individuals treated with anti-retroviral therapies, the incidence has increased among non-HIV populations due to the expanding use of corticosteroids and other immunomodulatory agents to treat immune-mediated inflammatory diseases and hematologic and solid malignancies. Despite the success of trimethoprim-sulfamethoxazole (TMP-SMX) prophylaxis, patients who are unable to tolerate treatment, take drugs where TMP-SMX is contraindicated, or experience breaks in daily compliance remain at risk. Immunocompromised populations would benefit from vaccine strategies that reduce morbidity and mortality due to acute PJP. MethodsHerein, we used a newly established non-human primate (NHP) model of Pneumocystis infection in the context of drug-induced immunosuppression to test the immunogenicity and protective efficacy of a vaccine strategy administered prior to and throughout drug-induced immunosuppression using the ‘pan-fungal’ vaccine candidate NXT-2a. Longitudinal blood and bronchoalveolar lavage sampling was performed to monitor anti-NXT-2a antibody titers, lymphocyte populations, and infection status. ResultsImmunization with NXT-2a prior to immunosuppression induced robust humoral immune responses in healthy outbred macaques. Subsequent therapeutic boosting throughout drug-induced immunosuppression prevented protective antibody titer decline. Our collective vaccination strategy provided significant protection against Pneumocystis infection throughout the duration of the study. DiscussionThese studies demonstrate the efficacy and feasibility of an NXT-2a based vaccination strategy in a NHP model with a planned immunosuppressive regimen. This strategy may be further applied toward other opportunistic fungal pathogens, such as Candida spp. and Aspergillus spp. in similarly immunosuppressed populations.